Cannabinoid Receptor‐2 Regulates Embryonic Hematopoietic Stem Cell Development via Prostaglandin E2 and P‐Selectin Activity. (26th May 2015) - Esain, Virginie; Kwan, Wanda; Carroll, Kelli J.; Cortes, Mauricio; Liu, Sarah Y.; Frechette, Gregory M.; Sheward, Lea M. V.; Nissim, Sahar; Goessling, Wolfram; North, Trista E.
Abstract Cannabinoids (CB) modulate adult hematopoietic stem and progenitor cell (HSPCs) function, however, impact on the production, expansion, or migration of embryonic HSCs is currently uncharacterized. Here, using chemical and genetic approaches targeting CB‐signaling in zebrafish, we show that CB receptor (CNR) 2, but not CNR1, regulates embryonic HSC development. During HSC specification in the aorta‐gonad‐mesonephros (AGM) region, CNR2 stimulation by AM1241 increased runx1;cmyb+ HSPCs, through heightened proliferation, whereas CNR2 antagonism decreased HSPC number; FACS analysis and absolute HSC counts confirmed and quantified these effects. Epistatic investigations showed AM1241 significantly upregulated PGE2 synthesis in a Ptgs2‐dependent manner to increase AGM HSCs. During the phases of HSC production and colonization of secondary niches, AM1241 accelerated migration to the caudal hematopoietic tissue (CHT), the site of embryonic HSC expansion, and the thymus; however these effects occurred independently of PGE2. Using a candidate approach for HSC migration and retention factors, P‐selectin was identified as the functional target of CNR2 regulation. Epistatic analyses confirmed migration of HSCs into the CHT and thymus was dependent on CNR2‐regulated P‐selectin activity. Together, these data suggest CNR2‐signaling optimizes the production, expansion, and migration of embryonic HSCs by modulating multiple downstream signaling pathways. Stem Cells2015;33:2596—2612